The Impact of External Environmental Factors, Entrepreneurial Motivation, Social Support, and Business Knowledge on the Success of Start-ups - Hartati, Hartati; Hasan, Zainol; Tawil, Dr Muhamad Risal; Aji, Lexi Jalu (IJBLE Scientific Publications Community Inc., 2024)
This research explores the intricate dynamics influencing the success of start-up ventures, focusing on the interactions between external environmental factors, entrepreneurial motivation, social support, and business knowledge. Through a quantitative approach and employing Partial Least Squares Structural Equation Modeling (PLS SEM), data from a diverse sample of 170 participants in Indonesia were analyzed. The results unveil significant positive relationships between sustainable marketing strategies, environmental awareness, and consumer preferences for eco-friendly products, highlighting the pivotal role of external factors and intrinsic drivers in shaping entrepreneurial endeavors. Additionally, the findings underscore the mediating role of environmental awareness in the relationship between sustainable marketing strategies and consumer preferences, emphasizing the importance of integrating sustainability principles into marketing strategies. These insights contribute to a deeper understanding of the multifaceted determinants of start-up success and offer actionable recommendations for fostering a conducive ecosystem for entrepreneurial growth and innovation in Indonesia.